2009
DOI: 10.1002/hep.23043
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic regulatory T cells and Kupffer cells are crucial mediators of systemic T cell tolerance to antigens targeting murine liver†

Abstract: The mechanisms of tolerance in the liver that limit susceptibility to food allergy and that mediate the acceptance of liver transplants even with a complete MHC mismatch remain poorly defined. Here we report that in a model of liver-directed gene transfer cytotoxic T lymphocyte (CTL) responses to non-self antigens are controlled by hepatic regulatory T cells (Tregs) that secrete the immunosuppressive cytokine interleukin (IL)-10 in response to the antigen. In addition, Kupffer cells (KCs), normally thought to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
184
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(192 citation statements)
references
References 38 publications
(35 reference statements)
6
184
2
Order By: Relevance
“…Previous studies have shown that Tregs play a critical role in liver tolerance (13,22,23); however, in our study, Foxp3 + Treg numbers did not change in HBV-carrier mice, and CD25 + Treg depletion did not influence HBV persistence (Fig. S3).…”
Section: Resultscontrasting
confidence: 70%
See 2 more Smart Citations
“…Previous studies have shown that Tregs play a critical role in liver tolerance (13,22,23); however, in our study, Foxp3 + Treg numbers did not change in HBV-carrier mice, and CD25 + Treg depletion did not influence HBV persistence (Fig. S3).…”
Section: Resultscontrasting
confidence: 70%
“…The liver induces antigen-specific tolerance by a series of mechanisms, including clonal deletion (similar to central tolerance), as well as induction of Tregs and inhibition of memory T-cell responses, which favor peripheral tolerance (6,22,(27)(28)(29). However, the precise mechanisms underlining liver tolerance are not fully understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…KC mediate immunosuppression by production of IL‐10, by expression of the negative co‐stimulator for T cell activation programmed cell death ligand‐1 (PD‐L1) 27 and by preventing cytotoxic lymphocyte responses 28. Those activities translate into induction of KC‐dependent protective immune tolerance in liver 29.…”
Section: Phages Kupffer Cells and Immune Homeostasismentioning
confidence: 99%
“…2 Nonparenchymal liver cells, including liver sinusoidal endothelial cells, dendritic cells (DCs) and Kupffer cells (KCs), have been shown to be responsible for the creation of a local immunosuppressive microenvironment, permitting immune effector cells, such as T cells, to deliver tolerogenic signals, which contributes to the tolerogenic properties of the liver. [3][4][5][6] However, the exact mechanisms for the hepatic immunosuppressive microenvironment remain to be fully understood.…”
mentioning
confidence: 99%